The Hand Behind the Invisible Hand: Dogmatic and Pragmatic Views on Free Markets and the State of Economic Theory - Karl Mittermaier (Bristol University Press, 2020)
Using Adam Smith's notion of an 'invisible hand', this extraordinary contribution identifies dogmatic versus pragmatic views of free markets. Published posthumously, with new contributions by Rod O'Donnell, Daniel B. Klein and Christopher Torr, this book outlines Mittermaier's main thesis and its relevance for ongoing debates within economics, politics, sociology and philosophy.
Keywords: 330; Adam Smith; free markets; government intervention; history of economic thought; philosophy of economics; Marktwirtschaft; Wirtschaftsliberalismus; Ökonomische Ideengeschichte